Melatonin: The potential avenues in dentistry [version 1; peer review: 2 approved, 1 approved with reservations] - DIYA KAMATH; ARADHYA SINHA; Dr. SANIDHYA S; Deepa Kamath (F1000Research)
Melatonin, the “sleep hormone,” shows significant promise in dentistry owing to its antioxidant, anti-inflammatory, and immunomodulatory properties. It is beneficial for treating periodontal disorders and aiding osseointegration of dental implants. Additionally, melatonin helps to manage dental anxiety, offering an alternative to traditional sedatives. Periodontal disease is orchestrated by bacterial plaques along with an exaggerated immune-inflammatory host response. Treatment of periodontitis not only involves the removal of plaque, but also aims to minimize the cytokine load and control the reactive oxygen species burden in the tissues, which would re-establish a healthy periodontium and a balanced bone metabolism. Melatonin is known to exert beneficial effects, such as regulation of circadian rhythm, bone remodeling, and antimicrobial effects. Recent studies have demonstrated the successful use of melatonin as an adjunct to mechanical debridement for the treatment of periodontal disease. Its various uses include systemic administration of melatonin after one-stage full-mouth Non-Surgical Periodontal Therapy in healthy subjects as well as patients. This article provides a summary of the various clinical applications of melatonin, describing its mechanism of action, uses, and potential avenues for future research in dentistry.